Performans Kerbau Lumpur dan Strategi Pengembangannya pada Daerah dengan Ketinggian Berbeda di Kabupaten Cianjur (PERFORMANCE ANALYSIS OF SWAMP BUFFALO AT DIFFERENT ALTITUDES IN CIANJUR DISTRICT AND ITS DEVELOPMENT STRATEGIES - ., Komariah; Sumantri, Cece; Nuraini, Henny; Nurdiati, Sri; Mulatsih, Sri (Jurnal Veteriner, 2016)
The research objectives were to analyze reproduction performance and productivity of swamp buffalofrom different altitudes in Cianjur and draw up a hierarchy of productivity strategy development usinganalysis of SWOT (Strength, Weakness, Opportunity, Threats) and Analytical Hierarchy Process (AHP)with four criteria: technology, costs, impact, and the response of farmers. Survey was conducted in Cianjurduring January-March 2014 by interview prepared questionnaires and direct observation of 63 buffalo farmers. Secondary data were also obtained from relevant agencies. Primary data were collected usingdirect observation of 139 reproductive female buffaloes then were further analyzed. A total of 58 buffaloesat their productive period were sampled and taken their morphometric data. Whilst 37 buffaloes weremeasured their frame size using Body Condition Score (BCS). The results showed that the reproductionperformance of buffaloes in the lowlands are not significantly different from those in the highland. The ageat first oestrus, first mating, first calving, gestation period were 25.6 months, 26.6 months, 38.7 months,11.8 months, respectively.. The oestrus period was 5.3 days, and post-partum mating interval was 54.6days. Differences in altitude and sex significantly affected (P <0.05) the morphometry assessment. Thebody weight of male buffaloes were found lower than the females both in highlands and lowlands (P<0.05).The body conditioning score of buffalo performance at highland was better compared to those in thelowland. Based on the SWOT analysis and AHP: (1) The main strategy is to improve the technology basedon the criteria of internal weakness by increasing scale holdings to seize opportunities buffalo meat selfsufficiency;(2) based on the criteria of cost and impact, the strategy was to cover threats over the professionout of the region by empowering farmers (facilitate increased productivity buffalo); (3) based on the responsecriteria, the primary strategy is to improve the quality of education of farmers by facilitating productivityimprovement opportunities to achieve self-sufficiency buffalo meat. The main development strategy basedon the four criteria: technology, cost, impact, and farmer response were increasing of buffalo ownershipscale, production facilities, and farmers education quality.
Keywords: performance; development strategy; swamp buffalo; different heights; Cianjur district